The Effectiveness of Autohemotherapy in Chronic Urticaria Treatment in the Dr. Mohammad Hoesin General Hospital and Pertamina Hospital Palembang - Nopriyati Husan; Sarah Diba Zulkarnain; Athuf Thaha; Maria Mayfinna Gozali; Tiar Marina Octyvani (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Chronic urticaria (CU) is one of the most common case found in dermatology and venereology and it decreases the quality of life. Autohemotherapy (AHT) is an innovative therapy that works by desensitization and activation of the local immune system, and it is effective for recurrent or refractory urticaria. AHT technique is simple, inexpensive, and does not require special expertise that can be done at all levels of health services in Indonesia. Purpose: to determine the effectiveness of AHT in the CU treatment. Methods: This was a clinical trial research with involving patients with CU in the Allergo-Immunology Clinic of Department of Dermatology and Venereology Dr. Mohammad Hoesin General Hospital (DV RSMH) and Pertamina Hospital Palembang. The Urticaria Activity Score (UAS7) and Dermatology Life Quality Index (DLQI) assessments were carried out on week 1 and week 10. Result: The research was conducted from 1 July - 30 September 2019 involving 72 eligible  patients with 2 dropouts (2.8%). The mean age was 47 years (15-72 years), with 46 (63.9%) are women. Chronic spontaneous urticaria (CSU) was the most frequent diagnosis observed in 64 people (88.9%). Adverse events included bruises at the injection site (n=1; 1.4%) and at the blood draw location (n=1; 1.4%). On week 1, mean UAS7 was 30.77 ± 2.46, mean DLQI 21.66 ± 3.60. By week 10, UAS7 and DLQI significantly decrease to 4.12 ± 2.89 and 2.51 ± 1.53 (p <0.005). Conclusion: There was a significant decrease in UAS7 and DLQI in chronic urticaria patients after receiving AHT therapy for 10 weeks. This research concluded AHT can serve as an option in chronic urticaria treatment.